A abordagem do conceito de natureza nas propostas curriculares de geografia dos estados de São Paulo e do Paraná: uma correlação entre a teoria e a prática - Santos, David Augusto (2012)
This dissertation it is a search on the approach of nature concept at the official guidelines of Geography from the states of Sao Paulo and Parana implanted at the school system in 2008 and how they were realized and practiced by the teachers of the basic schooling. At the public education the process of to teach and learn in the schools are mediated by the presence of two working pedagogical tools: the didactic book and the official curriculum.The latter is becoming every day a more controversial issue, as the teacher, because of public policies for education, has lost in the daily school. The concept comes from nature as the basis of this research study because of their relevance in the formation of geographical elementary education students and evaluate curricula as well as teaching, is a task that becomes essential today. So the curriculum has been gaining such centrality in educational policies that are developed without the proper dialogue with researchers in the field and those actually perform the curriculum in daily school life. The survey showed that there is a gap between what is proposed under the documents and what actually takes place in various classrooms across the country. And an assessment of concepts, among them the nature concept, only can be positive if it was understood as a process where should be subject of critical. We believe this is a possible way for its redefinition according to geographical experiences of students and teachers. Therefore, we can understand in this research a movement from theory to practice, analyzing whether the same is revealed while mere reproduction or as transforming praxis